The Presbyteral Council as an Expression of Synodality - Billing, Robert (Université Saint-Paul / Saint Paul University, 2022)
Synodality is undeniably a significant focus in the ecclesiology of Pope Francis. Although difficult to define, this ecclesiological model has enormous potential and yet poses a challenge to all the faithful as a constitutive key to understanding ecclesial ministry and governance. As a fresh phase in the reception of the Second Vatican Council, synodality generates a personal and pastoral conversion of mentalities and structures to a new way of proceeding in the Church where pastors and faithful pray, meet, work together, take counsel together, and build up consensus. This thesis offers possibilities to promote synodality by encouraging and developing participative structures at the level of the particular Church. Indeed, the principal objective of this dissertation is to examine the possibility of refashioning aspects of the presbyteral council in accordance with the ecclesiogenesis that comes from the current synodalisation of the Church. In order to achieve this objective, the thesis reviews the significance of synodality and its ramifications for ecclesial renewal and reform (chapter one). The study identifies the participative structures in the particular Church, their limitations, and possible remedies. The dissertation recognises the critical role of the diocesan bishop and the priests in promoting and cultivating synodality in the particular Church; it underscores that a renewed and accentuated initial and ongoing formation in synodality for future and current pastors is imperative (chapter two). The thesis grounds the theological and juridical significance of the presbyteral council in history. It reviews the council’s mission and functions in the ius vigens, it explores some possibilities to overcome the challenges the council faces, and it proposes a new consensus model for the council’s functioning (chapter three). The study concludes by considering whether or not examining the governing council (regiminis consilium) of the Personal Apostolic Administration of St John Vianney and the three Personal Ordinariates for former Anglicans provides a model from which the presbyteral council might learn in order to enhance and intensify its synodal modus agendi (chapter four).
Keywords: Synodality; Presbyteral Council